2015
DOI: 10.1165/rcmb.2014-0448oc
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Retinoic Acid Receptor Beta by Interleukin-15 in the Lung during Cigarette Smoking and Influenza Virus Infection

Abstract: Virus-induced exacerbations often lead to further impairment of lung function in chronic obstructive pulmonary disease. IL-15 is critical in antiviral immune responses. Retinoic acid (RA) signaling plays an important role in tissue maintenance and repair, particularly in the lung. We studied RA signaling and its relation to IL-15 in the lung during cigarette smoke (CS) exposure and influenza virus infection. In vivo studies show that RA signaling is diminished by long-term CS exposure or influenza virus infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…In the present study, we show that inflammatory cytokines including IL-6 and IL-8 expression levels are increased significantly in the blood and sputum from COPD patients with viral exacerbation compared with stable patients. Using mouse models, our previous studies have shown that viral infection after CS exposure induces exaggerated lung inflammation [ 10 , 11 ], suggesting that CS and viruses might activate common pathways that lead to synergistic changes in certain mediators and subsequently an enhanced inflammatory response. In the present study, we mainly explored the roles of BRD4 in this exaggerated inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we show that inflammatory cytokines including IL-6 and IL-8 expression levels are increased significantly in the blood and sputum from COPD patients with viral exacerbation compared with stable patients. Using mouse models, our previous studies have shown that viral infection after CS exposure induces exaggerated lung inflammation [ 10 , 11 ], suggesting that CS and viruses might activate common pathways that lead to synergistic changes in certain mediators and subsequently an enhanced inflammatory response. In the present study, we mainly explored the roles of BRD4 in this exaggerated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have explored the effects of viral infection after CS exposure on the lung in mouse models, suggesting that CS and viruses interact in a manner to induce exaggerated lung inflammation [ 10 , 11 ]. However the molecular mechanisms are complex, it has not been fully addressed whether these two challenges (CS and viruses) activate common pathways that can lead to synergistic changes in certain mediators and subsequently an enhanced inflammatory response in the lung.…”
Section: Introductionmentioning
confidence: 99%
“…However, animal experiments show that CS has both proinflammatory and immunosuppressive effects, depending on smoking length, smoking dose, virus dose, IAV strain, and sample collection time (Table 1). As an example, the length of CS exposure in mouse models may be as short as 3 days or as long as 6 months prior to IAV infection [72,73]. Notes: h = hour(s); d = day(s); wk = week.…”
Section: In Vivo Animal Smoking Studiesmentioning
confidence: 99%
“…Here, we used a unique 2-hit model of CS exposure followed by a mild-dose of intranasal IAV infection in mice (20,21,23,24) that led to more severe lung injury than IAV infection alone. Using quantitative fluorescence intravital lung microscopy (qFILM) in live mice (25)(26)(27)(28)(29), we reveal for the first time to our knowledge that the prior exposure to CS exacerbates flu-induced lung injury by promoting lung microvascular occlusion by large platelet-rich neutrophil-platelet aggregates (NPAs), leading to the development of pulmonary ischemia followed by vascular leakage.…”
Section: Introductionmentioning
confidence: 99%